AI-Supported Identification of Project Managers’ Communication Focus and Style - Koivisto, Matti (International Journal of Advanced Corporate Learning (iJAC), 2026)
In companies engaged in project business, effective communication is crucial for successful projects implementation. However, project communication is not only limited to the management and leadership of the individual projects, but also encompasses factors related to the broader business environment. Therefore, effective communication requires not only understanding different perspectives but also identifying and adapting communication styles to different situations and stakeholders. This paper describes an exercise developed to identify the communication styles and focus areas of the project managers. The exercise is based on the principles of active learning, and it uses artificial intelligence to provide personalized feedback to the users. With the help of feedback, users identify the characteristics of their own way of communicating and possible development areas in their professional communication skills.